2021
DOI: 10.3390/jof7060456
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Use in Children: Therapeutic Drug Monitoring and Control of Inflammation as Key Points for Optimal Treatment

Abstract: Voriconazole plasma concentrations (PC) are highly variable, particularly in children. Dose recommendations in 2–12-year-old patients changed in 2012. Little data on therapeutic drug monitoring (TDM) after these new recommendations are available. We aimed to evaluate voriconazole monitoring in children with invasive fungal infection (IFI) after implementation of new dosages and its relationship with safety and effectiveness. A prospective, observational study, including children aged 2–12 years, was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Of all the included studies, one included only orally administered formulations, 32 one included only intravenously administered formulations, 28 and the remaining 18 included both orally and intravenously administered formulations. For detecting inflammatory cytokines, 17 studies used CRP, 16,23,25,27–30,32–41 16 studies used only CRP, one study used CRP in combination with other inflammatory factors (IL‐6, IL‐8, IFN‐γ, IL‐10, IL1‐RA, IL‐1β and TNF‐α), 39 two studies used PCT, 24,26 and one study used only inflammatory factors (IL‐1β, IL‐6, IL‐18, INF‐γ, TNF‐α and TGF‐β1) 31 . Regarding the VRZ concentration detection methodology, 12 studies used LC/MS, 16,23–27,30,31,34,35,37,40 seven studies used HPLC, 29,32,33,36,38,39,41 and one study used enzyme immunoassay 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the included studies, one included only orally administered formulations, 32 one included only intravenously administered formulations, 28 and the remaining 18 included both orally and intravenously administered formulations. For detecting inflammatory cytokines, 17 studies used CRP, 16,23,25,27–30,32–41 16 studies used only CRP, one study used CRP in combination with other inflammatory factors (IL‐6, IL‐8, IFN‐γ, IL‐10, IL1‐RA, IL‐1β and TNF‐α), 39 two studies used PCT, 24,26 and one study used only inflammatory factors (IL‐1β, IL‐6, IL‐18, INF‐γ, TNF‐α and TGF‐β1) 31 . Regarding the VRZ concentration detection methodology, 12 studies used LC/MS, 16,23–27,30,31,34,35,37,40 seven studies used HPLC, 29,32,33,36,38,39,41 and one study used enzyme immunoassay 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the following factors: (1) the hepatic blood flow in children is higher than that in adults; (2) the first‐pass effect of VRZ in children is more obvious; (3) the protein expression level of CYP2C19 in children's liver tissue is higher than that in adults 46,47 ; and (4) the activity of flavin monooxygenase 3 (FMO3) in liver microsomes in children aged 2–10 years is different from that in adults 48 . However, the results of another two studies in children were inconsistent with these findings; in one study, the CRP levels were not significantly related to VRZ concentrations, 25 while in the other, elevated CRP levels were significantly associated with insufficient VRZ concentrations 41 . However, the above study populations were limited to children over 2 years old, probably because VRZ is only officially approved for adults and children ≥2 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The authors established the median dose by age ≤6, 7-12.9, ≥13 as follows: 8.1, 6.7, and 3.3 mg/kg. Recently, another TDM study including 27 children aged 2-12 years, was performed [42]. The authors aimed to evaluate VCZ monitoring in children with IFIs after the administration of new dosages.…”
Section: The Optimal Dosage Regimenmentioning
confidence: 99%
“…Low plasma VCZ levels were observed until carbamazepine was discontinued from treatment. In recent studies on the pediatric population, the association between C-reactive protein levels (CRP) and C trough was observed [42,50,51]. Luo et al reported a significant correlation of CRP and C trough VCZ for children in age 11-18 years but not in the age of 2-10 years.…”
Section: Factors Affecting Serum Concentration In Tdmmentioning
confidence: 99%
See 1 more Smart Citation